The Gospel of Matthew; v. 1 chapters 1to10 - Barclay, William, 1907-78 (Edinburgh, Scotland Saint Andrew, 1975)
Includes bibliographical references.
Copy 2 1987 reprint
Keywords: Bible. N.T. Matthew I-X -- commentaries